A novel potent metal-binding NDM-1 inhibitor was identified by fragment virtual, SPR and NMR screening. Issue 9 (1st May 2020) - Guo, Huifang; Cheng, Kai; Gao, Yan; Bai, Weiqi; Wu, Cai; He, Wei; Li, Conggang; Li, Zhuorong
Graphical abstract: A novel scaffold of NDM-1 inhibitors is described. The scaffold was discovered from metal-binding pharmacophore enriched library with virtual and SPR screen. Solution NMR found that the scaffold binds to the NDM-1 active pocket and the zinc ion in the pocket. Design and syntheses found compounds with synergistic antibacterial activity. Abstract: NDM-1 can hydrolyze nearly all available β -lactam antibiotics, including carbapenems. NDM-1 producing bacterial strains are worldwide threats. It is still very challenging to find a potent NDM-1 inhibitor for clinical use. In our study, we used a metal-binding pharmacophore (MBP) enriched virtual fragment library to screen NDM-1 hits. SPR screening helped to verify the MBP virtual hits and identified a new NDM-1 binder and weak inhibitor A1 . A solution NMR study of 15 N-labeled NDM-1 showed that A1 disturbed all three residues coordinating the second zinc ion (Zn2) in the active pocket of NDM-1. The perturbation only happened in the presence of zinc ion, indicating that A1 bound to Zn2. Based on the scaffold of A1, we designed and synthesized a series of NDM-1 inhibitors. Several compounds showed synergistic antibacterial activity with meropenem against NDM-1 producing K. pneumoniae .